solve 6x+9=8

6x+9=8 6x = 8 - 9 6x = -1 x = -1/6

Question

Asked 1/12/2014 2:10:24 PM

Updated 1/12/2014 2:34:21 PM

1 Answer/Comment

Rating

3

6x+9=8

6x = 8 - 9

6x = -1

x = -1/6

6x = 8 - 9

6x = -1

x = -1/6

Added 1/12/2014 2:34:21 PM

This answer has been confirmed as correct and helpful.

Simplify.
(4x)2 + 42x

Question

Expert Answered

Updated 1/9/2014 3:40:01 PM

1 Answer/Comment

Simplified (4x)2 + 42x is 50x.

Added 1/9/2014 3:40:01 PM

This answer has been confirmed as correct and helpful.

Simplified expression for 4(x - 8) - 2(x - 3) + 3x.

Question

Not Answered

Updated 55 days ago|5/22/2018 6:50:43 AM

1 Answer/Comment

4(x - 8) - 2(x - 3) + 3x

= 4x - 32 - 2x + 6 + 3x

= 2x - 26 + 3x

= 5x - 26

= 4x - 32 - 2x + 6 + 3x

= 2x - 26 + 3x

= 5x - 26

Added 55 days ago|5/22/2018 6:50:43 AM

This answer has been confirmed as correct and helpful.

solve the inequality 0.2(0.1x + 0.9) < -0.8

Question

Not Answered

Updated 1/11/2014 12:48:54 AM

1 Answer/Comment

0.2(0.1x + 0.9) < -0.8

0.02x + 0.18 < -0.8

0.02x < -0.8 - 0.18

0.02x < -0.98

x < -49

0.02x + 0.18 < -0.8

0.02x < -0.8 - 0.18

0.02x < -0.98

x < -49

Added 1/11/2014 12:48:52 AM

This answer has been confirmed as correct and helpful.

27,082,036

questions answered

There are no comments.